THE ROLE OF PSYCHOEDUCATION IN EMOTION REGULATION TO IMPROVE THE ABILITY TO MANAGE EMOTIONS IN AL-INSAN WONOAYU ORPHANAGE CHILDREN - Maharani, Yusrilda; Ansyah, Eko Hardi (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the effectiveness of psychoeducation in enhancing emotional regulation among children residing in the Al-Insan Wonoayu Orphanage. Method: Utilizing an experimental design with a one-group pretest-posttest approach, the study involved 22 children who participated in multiple psychoeducational sessions. The intervention focused on recognizing emotions, managing both positive and negative emotions, coping with emotional stress, and applying relaxation techniques grounded in Islamic values. Emotional regulation was measured using a standardized scale before and after the intervention. Results: Paired samples t-test results indicated a significant improvement in emotional regulation, with pretest scores (M = 99.45, SD = 8.996) rising to posttest scores (M = 116.86, SD = 17.734); t(21) = -4.803, p < 0.001. The effect size (Cohen’s d = -1.024) suggests a large impact of the intervention. Novelty: This study provides empirical support for the integration of psychoeducational approaches with Islamic values to foster emotional regulation in vulnerable child populations. It highlights the contextual effectiveness of culturally sensitive interventions in orphanage settings, offering a valuable model for psychosocial programs in similar environments.